STRUKTUR BIAYA, KEUNTUNGAN, DAN NILAI TAMBAH AGROINDUSTRI GULA KELAPA DI KECAMATAN NEGERI KATON KABUPATEN PESAWARAN - Ayla Vilin Windyata; Dwi Haryono; Maya Riantini (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This research aims to analyze the structure of costs, profit, and added value of coconut agroindustry.  This research was a survey method of 38 coconut sugar agroindustries in Negeri Katon Subdistrict, Pesawaran Regency.  The data of this research were collected in December 2019 - January 2020.  The analytical methods used in this research were cost structure analysis of total costs, profit analysis based on revenue and total costs, and Hayami added value analysis.  The results of this research indicated that the biggest cost component of the cost structure of coconut sugar production were palm juice (44.21%), then followed by labor cost (24.22%), firewood cost (15.43%), transportation cost (8.45%), wooden box cost (3.47%), tool depreciation cost (1.67%), sodium cost (1.55%), plastic cost (0.69%), and whiting cost (0.31%).  Coconut sugar agroindustry in Negeri Katon Subdistrict Pesawaran Regency received profit as much as IDR1,549,174.33/month.  Added value of coconut sugar was IDR1,111.22/liter of raw material.  It indicated that coconut sugar agroindustry in Negeri Katon Subdistrict Pesawaran Regency had a positive added value and feasible to be developed.Key words: agroindustry, coconut sugar, cost structure, profit, added value